Attenuation of 1-Methyl-4-Phenyl-1, 2,3,6-Tetrahydropyridine induced nigrostriatal toxicity in mice by N-Acetyl Cysteine - Sharma, A.; Kaur, P.; Kumar, V.; Gill, K. D. (Cellular and Molecular Biology, 2007)
The present study was designed to investigate the effects of N-acetyl cysteine (NAC), an antioxidant on 1-methyl 4-phenyl-1,2,3,6 tetrahydropyridine (MPTP) induced neurotoxicity in the nigrostriatal dopaminergic system of mice. MPTP treatment caused 80% decrease of the dopamine levels in the striatum of C57BL/ 6J mice. A marked increase in the extent of lipid peroxidation, superoxide dismutase (SOD) and g-glutamyl transpeptidase (g-GTP) was seen, while a significant decrease in the levels of glutathione (GSH), total thiols and glutathione peroxidase (GPx) activity was observed in the substantia nigra pars compacta (SNpc) of MPTP treated animals. As compared to control animals, Co-administration of NAC with MPTP restored the depleted dopamine, GSH, total tissue thiol levels and GPx activity in SNpc of treated mice brain. Moreover, NAC treatment also provided protection against lipid peroxidation and superoxide dismutase activity. The results of present study suggested that NAC attenuates MPTP neurotoxicity in mice brain and this protection by the NAC might be contributing to the regeneration of GSH, a major antioxidant.